Association of Neighborhood Alcohol Environment With Alcohol Intake and Cardiovascular Risk Factors in India: Cross-Sectional Evidence From APCAPS - Li, Yingjun; Mallinson, Poppy Alice Carson; Aggarwal, Aastha; Kulkarni, Bharati; Kinra, Sanjay (Frontiers in Cardiovascular Medicine, 2022)
There is more and more proofs about the impact of neighborhood alcohol environment on alcohol-associated events. The relationship between the neighborhood availability and accessibility of alcohol outlet with individual level of alcohol consumption along with 11 cardiovascular risk factors was explored for the first time in India using data from the 3rd follow-up of the APCAPS (n=6156, for liquor intake and 5641 for heart and blood vessel risk elements). In fully adjusted models, in contrast to volunteers at the lowest tertile, those at the highest tertile of distance to the closest alcohol outlet were more probably to exhibit less alcohol consumption (-14.40 g/day, 95% CI: -26.21, -2.59). A unit per km2 rise in alcohol outlet density in 400m buffering area was related to a rise in waist circumference (1.45 mm, 95% CI: 0.13, 2.77), SBP (0.29 mmHg, 95% CI: 0.09, 0.49), and DBP (0.19 mmHg, 95% CI: 0.03, 0.35). A unit per 100m rise in distance to the closest alcohol outlet was related to a rise in waist circumference (-2.39 mm, 95% CI: -4.18, -0.59), SBP (-0.41 mmHg, 95% CI: -0.68, -0.15), and DBP (-0.29 mmHg, 95% CI: -0.51, -0.07). Neighborhood availability of alcohol outlets within immediate locality of participants' households had a closer relationship with cardiovascular risk factors than that within the whole village. Public health policies designed to limit neighborhood availability and accessibility of alcohol outlets ought to be advocated in southern India.